Very early neurological deterioration during intravenous thrombolysis in patients with acute ischemic stroke - Ying-Chi Shen; Shin-Joe Yeh; Chih-Hao Chen; Sung-Chun Tang; Li-Kai Tsai; Jiann-Shing Jeng (Journal of the Formosan Medical Association)
Background: Neurological deterioration within 24 h after intravenous thrombolysis with tissue plasminogen activator (tPA) is associated with poor outcomes in patients with acute ischemic stroke (AIS). This study aimed to elucidate the features of neurological deterioration specifically during tPA infusion in these patients. Methods: We analyzed patients with AIS receiving thrombolysis between January 2018 and December 2021. Very early neurological deterioration (VEND) was defined as an increase of 4 or more points in the National Institutes of Health Stroke Scale (NIHSS) score during tPA infusion. Poor functional outcome was defined as a modified Rankin Scale score of 3–6 at three months. Results: Among the 345 patients with AIS who received tPA, 8.4% had VEND; all of which were caused by ischemic progression. Patients with VEND had a higher prevalence of intracranial atherosclerotic disease (41% vs. 17%, P = 0.005). VEND independently predicted poor functional outcome in both groups with minor (NIHSS score <6) and non-minor (NIHSS score >6) stroke. Among patients with minor stroke, those with VEND were more likely to undergo endovascular thrombectomy (EVT) than those without (38% vs. 5%, P = 0.019). In patients receiving EVT after VEND, the NIHSS scores at 24 h, which were correlated with 3-month functional outcome, were lower in those with successful recanalization than in those without (12 ± 9 vs. 26 ± 7, P = 0.047). Conclusion: VEND predicted poor functional outcomes in patients with AIS. Timely and successful recanalization using EVT potentially alleviates the negative impact of VEND on long-term outcomes.